2016
DOI: 10.3928/01477447-20160714-06
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts and the Role of Surgery in the Treatment of Jumper's Knee

Abstract: Jumper's knee is a common cause of anterior knee pain among athletes and active populations. Numerous treatments have been described with variable results. To better delineate this, the authors reviewed all articles from 2000 to 2014 pertaining to the treatment of patellar tendinopathy, focusing namely on treatment of recalcitrant cases. Open and arthroscopic techniques were found to achieve similar satisfactory results in 81% (range, 45%-100%) and 91% (range, 86%-96%) of patients, respectively. Average time t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…their previous level when bony resection was performed compared with 68.7% when it was not 13 . RTS time may be a potential area where arthroscopic surgery yields better results compared with open proce-dures 24 . A systematic review by Khan and Smart reported that patients who underwent arthroscopic surgery had an average RTS time of 3.8 months, compared with 5.5 months in the open surgery group, with this difference being statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…their previous level when bony resection was performed compared with 68.7% when it was not 13 . RTS time may be a potential area where arthroscopic surgery yields better results compared with open proce-dures 24 . A systematic review by Khan and Smart reported that patients who underwent arthroscopic surgery had an average RTS time of 3.8 months, compared with 5.5 months in the open surgery group, with this difference being statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there is still no consensus on the best surgical treatment for chronic patellar tendinopathy. According to the published studies both surgeries give satisfactory results with success rate of more than 77% but arthroscopic surgery gives fewer complications, faster return to preinjury level of sport activities and a non-significant higher success rate [12,14,[23][24][25][26]. Multiple tenotomies and excision of a portion of the tendon can theoretically decrease mechanical properties of the tendon prolonging the patient's return to full function and sports, especially when dealing with athletes, who expect to gain an excellent result to compete at a high level and to practice daily with infrequent rest increasing the risk of failure.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, insertional tendinopathies such as QT and PT rupture and jumper’s knee are difficult to repair and treat. 6,17 The QT and PT, including part of the patella, are used as grafts in ACL reconstructions 4,8 and are difficult to regenerate. 5,15 Our results suggest consideration of appropriate treatment strategies based on age and the development of new treatment methods for regeneration of the tendon-bone interface and insertions.…”
Section: Discussionmentioning
confidence: 99%